The diversity and distribution of Holothuroidea in shallow waters of Baluran National Park, Indonesia - ARIF MOHAMMAD SIDDIQ; TRI ATMOWIDI; IBNUL QAYIM (Society for Indonesian Biodiversity, 2016)
Siddiq AM, Atmowidi T, Qayim I. 2015. The diversity and distribution of Holothuroidea in shallow waters of BaluranNational Park, Indonesia. Biodiversitas 17: 55-60. A study of the diversity and distribution of sea cucumber (Holothuroidea) in shallow waters at Baluran National Park, East Java, Indonesia was carried out from July until September 2015. The method used in this studywas systematic transect in low tide condition. Samples were collected by hands at intertidal sites. Identification of sea cucumber species based on morphological ossicles. Twenty one species of Holothuroidea belonging two orders and four families were found in this study. The most dominant family found was Holothuriidae (16 species), followed by Stichopodidae (2 species), Synaptidae (2 species), and Chiridotidae (1 species). Four species (Holothuria olivacea, H. verrucosa, Labidodemas rugosum, and Chiridota smirnovi) are new record for Java waters and one species (H. papillifera) is a new record for Indonesian waters. Two morphospecies (H. aff. macroperona and Stichopus cf. monotuberculatus) need reconfirmation to species level. The highest abundance species of Holothuroidea was found at under rock with 15 species. Whereas, the highest number of individuals was found in seagrass areas with 5457 individuals. H. atra has extensive habitat distribution, such as seagrass, macroalgae, coral reef, dead coral, sand, and under rock.